Changes in Glomerular Volume, Sclerosis, and Ischemia at 5 Years after Kidney Transplantation: Incidence and Correlation with Late Graft Failure. Issue 2 (17th February 2023) - Denic, Aleksandar; Bogojevic, Marija; Subramani, Rashmi; Park, Walter D.; Smith, Byron H.; Alexander, Mariam P.; Grande, Joseph P.; Kukla, Aleksandra; Schinstock, Carrie A.; Bentall, Andrew J.; Rule, Andrew D.; Stegall, Mark D.
Abstract : Abstract : Significance Statement: Glomerular volume, ischemic glomeruli, and global glomerulosclerosis are not consistently assessed on kidney transplant biopsies. The authors evaluated morphometric measures of glomerular volume, the percentage of global glomerulosclerosis, and the percentage of ischemic glomeruli and assessed changes in these measures over time to determine whether such changes predict late allograft failure. All three features increased from transplant to five-year biopsy. Kidneys with smaller glomeruli at 5 years had more global glomerulosclerosis and a higher percentage of ischemic-appearing glomeruli. Smaller glomeruli and increasing percentages of global glomerulosclerosis and ischemic glomeruli at 5 years predicted allograft failure. Only increased percentage of ischemic glomeruli predicted allograft failure at 5 years independent of all Banff scores. Glomerular changes reflect pathologic processes that predicted allograft loss; measuring them quantitatively might enhance the current Banff system and provide biomarkers for intervention trials. Background: Histology can provide insight into the biology of renal allograft loss. However, studies are lacking that use quantitative morphometry to simultaneously assess changes in mean glomerular volume and in the percentages of globally sclerosed glomeruli (GSG) and ischemic-appearing glomeruli in surveillance biopsies over time to determine whether such changes are correlated with late graft failure. Methods: We used digital scans of surveillance biopsies (at implantation and at 1 and 5 years after transplantation) to morphometrically quantify glomerular volume and the percentages of GSG and ischemic-appearing glomeruli in a cohort of 835 kidney transplants. Cox proportional hazards models assessed the risk of allograft failure with these three glomerular features. Results: From implantation to 5 years, mean glomerular volume increased by nearly 30% (from 2.8×10 6 to 3.6×10 6 µm 3 ), mean percentage of GSG increased from 3.2% to 13.2%, and mean percentage of ischemic-appearing glomeruli increased from 0.8% to 9.5%. Higher percentages of GSG and ischemic-appearing glomeruli at 5-year biopsy predicted allograft loss. The three glomerular features at 5-year biopsy were related; the percentage of GSG and the percentage of ischemic glomeruli were positively correlated, and both were inversely correlated to glomerular volume. At 5 years, only 5.3% of biopsies had ≥40% ischemic glomeruli, but 45% of these grafts failed (versus 11.6% for <40% ischemic glomeruli). Higher Banff scores were more common with increasing percentages of GSG and ischemia, but at 5 years, only the percentage of ischemic glomeruli added to predictive models adjusted for Banff scores. Conclusions: Glomerular changes reflect important pathologic processes that predict graft loss. Measuring glomerular changes quantitatively on surveillance biopsies, especially the proportion of ischemic-appearing glomeruli, may enhance the current Banff system and be a useful surrogate end point for clinical intervention trials. Podcast: This article contains a podcast at